GRAMMATICAL FUNCTIONS IN INDONESIAN RELATIVE CLAUSES IN FOREIGN STUDENTS’ WRITING - Anggun Melati Sari; Andayani Andayani; Sumarlam Sumarlam (Pusat Kajian Humaniora FBS Universitas Negeri Padang, 2017)
This study aims to describe the grammatical function of the Indonesian relative clauses found on the foreign students' academic degree program at Technical Manager Unit Language (UPTBahasa) University Sebelas Maret Surakarta. Data used in the form of writing, the sentences in the written essays of foreign students contained relative clauses. The techniques of data analysis use apportion method and advanced techniques of apportion method. The result of this study shows that the process of relativization that occurs in Indonesian can only relate the subject function. As the development of linguistics, the process of relativizationalso occurs in the object. Relativization on object will be accepted when it is altered through the passage process. In addition, the process of relativizationthat occurs can be through the steps, namely the obliteration strategy. The obliteration strategy serves to dissipate the nominative which relating its relative clauses. This research has concluded that the relativization process of relative clauses in Indonesian only occurs in the subject. Then, the most frequently used relativization in Indonesian is the obliteration strategy.Keywords: Indonesian for foreign speakers, grammatical functions, strategy obliteration, relative clausesFUNGSI GRAMATIKAL DALAM KLAUSA RELATIF BAHASA INDONESIA PADA KARANGAN MAHASISWA ASINGAbstrakPenelitian ini bertujuan untuk mendiskripsikan tentang fungsi gramatikal klausa relatif bahasa Indonesia yang ditemukan pada karangan mahasiswa asing program darmasiswa level akademik di UPT Bahasa Universitas Sebelas Maret Surakarta. Data yang digunakan berupa data tulis, yakni kalimat-kalimat dalam karangan mahasiswa asing yang didalamnya terdapat klausa relatif. Teknik analisis data menggunakan metode agih dan teknik lanjutan dari metode agih. Hasil penelitian ini menunjukkan bahwa proses perelatifan yang terjadi dalam bahasa Indonesia hanya dapat merelatifkan fungsi subjek. Seiring perkembangan ilmu kebahasaan, proses perelatifan terjadi juga pada objek. Perelatifan pada objek akan berterima apabila diubah melalui proses pemasifan. Selain itu, proses perelatifan yang terjadi dapat melalui langkah-langkah, yakni strategi obliteration. Strategi obliteration berfungsi untuk melesapkan nomina yang direlatifkan dalam klausa relatifnya. Penelitian ini memeroleh simpulan bahwa proses perelatifan klausa relatif dalam bahasa Indonesia hanya terjadi pada subjek. Kemudian, strategi perelatifan dalam bahasa Indonesia yang sering digunakan adalah strategi obliteration. Kata Kunci: bahasa Indonesia bagi penutur asing, fungsi gramatikal, strategi obliteration, klausa relatif